The Role of the Factor X Activation Peptide: A Deletion Mutagenesis Approach - Rudolph, Amy E.; Mullane, Michael P.; Porche-Sorbet, Rhonda; Daust, Heather A.; Miletich, Joseph P. (Thrombosis and Haemostasis, 2002)
To understand the role of the factor X (fX) activation peptide (AP), a deletion mutagenesis approach was employed. Two single-chain, variant enzymes were generated in which 41 residues were deleted from the AP: fXdes-137-183 and fXdes-137-183;N191A, which lacks a carbohydrate moiety at Asn191 due to an alanine substitution. Deletion of the fX AP did not impact fXa catalytic activity. Activation of the variant zymogens, however, was altered. Neither mutant enzyme was activated by the fX coagulant protein from Russell’s viper venom (RVV-X1). Activation by factor VIIa (fVIIa) and fVIIa in the presence of cofactor, lipidated tissue factor (TF), occurred at an accelerated rate for both variants as compared to wild-type fX (WTfX). Similar to fVII, the mutants auto-activated in a cofactor-independent manner, which was characterized by a lag period and accelerated dose-dependently by plasma fXa (kcat/Km, 0.046 ± 0.004 µM−1s−1). Both mutants were also found to be activated by fVIIa (0.31 ± 0.03 µM−1s−1), fIXa (0.30 ± 0.03 µM−1 s−1), and thrombin (0.00078 ± 0.00015 µM−1s−1). In all cases, the rate of activation was faster for fXdes-137-183;N191A as compared to fXdes-137-183. We propose that the fX AP and Asn191 carbohydrate serve primarily as negative autoregulation mechanisms to prevent spurious activation of fX and secondarily in cofactor dependence and activator specificity.The abbreviations used are: TF, human tissue factor; AP, activation peptide; HEPES, (N-[2-Hydroxyethyl]piperazine-N’-[2-ethanesulfonic acid]); PEG, polyethylene glycol 8000; BSA, bovine serum albumin; Tris, (Tris[hydroxymethyl] aminomethane); EDTA, (Ethylenedinitrilo)-tetraacetic acid; SDSPAGE, sodium dodecyl sulfate polyacrylamide gel electrophoresis; RVV-X, X activating protein from Russell’s viper venom; gla, γ-carboxylated glutamic acid; WTfX, wild type factor X; PC:PS, phosphatidylcholine:phosphatidylserine; fXa, fIXa, f Va, fVIIa, and fVIIIa, activated coagulation factor X, IX, V, VII, and VIII; ATIII, antithrombin; TFPI, tissue factor pathway inhibitor.
Keywords: Factor X; activation peptide; deletion